1997
DOI: 10.1038/sj.gt.3300477
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids augment the bystander effect in vitro and in vivo in herpes simplex virus thymidine kinase/ganciclovir-mediated gene therapy

Abstract: Metabolic cooperation via gap junctional intercellular comtransduced with HSVtk via either retrovirus or adenovirus munication (GJIC) is an important mechanism of the vectors. This augmentation of bystander effect could also bystander effect in gene therapy using the herpes simplex be seen in vivo. HSVtk-transduced tumors in mice treated virus thymidine kinase/ganciclovir (HSVtk/GCV) 'prodrug' with the combination of GCV and retinoids were signifisystem. Since retinoids have been reported to increase cantly sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 5 publications
2
30
0
1
Order By: Relevance
“…By upregulating connexin-43 expression and thus enhancing gap junctional intercellular coupling (GJIC), retinoic acid was able to increase bystander cell killing. 20 In this respect, it should be noted that GJIC is often down-regulated in tumors. 21 Another approach may be based on the identification of new nucleoside analogues that possess superior bystander killing capabilities.…”
Section: Correspondence: J Balzarini Rega Institute For Medical Resementioning
confidence: 99%
See 1 more Smart Citation
“…By upregulating connexin-43 expression and thus enhancing gap junctional intercellular coupling (GJIC), retinoic acid was able to increase bystander cell killing. 20 In this respect, it should be noted that GJIC is often down-regulated in tumors. 21 Another approach may be based on the identification of new nucleoside analogues that possess superior bystander killing capabilities.…”
Section: Correspondence: J Balzarini Rega Institute For Medical Resementioning
confidence: 99%
“…The procedure to evaluate the bystander effect of the compounds was modified from Park et al 20 as follows. OstTK − cells were mixed with HSV-1 tk-GFP gene-transfected cells in percentages ranging from 0 to 100% (0, 0.2, 1, 5, 10, 25, 50, 75, 90 and 100%) transfected cells.…”
Section: Bystander Effectmentioning
confidence: 99%
“…Recently, enhancement of the bystander effect on killing of mouse mesothelioma cells by GCV in vivo by treating mice with retinoic acids was correlated with increased Cx43 expression and GJIC capacity in vitro. 30 It thus appears that induction of GJIC can provide a useful increase in the bystander effect and compensate for the low number of tumor cells that incorporate the HSVtk gene when classical viral vectors are used. Since low communication capacity seems to be a common feature of the cancer cell phenotype, 31 it is crucial to make such cells communicate more in situ either by directly injecting GJIC enhancers or by introducing functional connexin genes into the tumor cells.…”
Section: Figure 4 Hsv-tk and Cx43 Mrna Expression In Tumors Ofmentioning
confidence: 99%
“…[27][28][29] Therefore, pharmacological strategies aiming at upregulating the level of connexins have been proposed in order to increase the BE. [30][31][32][33][34][35] The delivery of connexin genes together with TK has also been evaluated, and it has been shown that the BE could be induced in gap junction deficient cancer cells. 26,36 A very different type of BE that is independent of the level of connexins has been recently reported.…”
Section: Introductionmentioning
confidence: 99%